Ten Years on from the Global Financial Crisis – a Reflection on the Treatment of Insolvent Financial Institutions in the UK and EU - Moffatt, P. (Bulletin of Yerevan University C: Jurisprudence, 2019)
My theme for today is to reflect upon the work that has been undertaken in the UK and the EU in relation to the treatment of insolvent financial institutions in the aftermath of the global financial crisis that was still at its height a decade ago, in 2009. Since this is a vast topic and, I appreciate, a highly specialist one in the context of this conference, this paper can only provide a brief introduction. I hope, however, that it will provide a starting point for any student interested in furthering their understanding of this fascinating area of law. As a framework for this reflection, I will begin with a consideration of the financial sector safety net as it was in the UK in the period before the financial crisis and, using the failure of Northern Rock bank as an example, demonstrate how it has changed, both through UK “home grown” legislation as well as through EU legislation.1 I will then reflect upon whether it is likely that, as Mark Carney, Governor of the Bank of England and then Chair of the Financial Stability Board stated in November 2014: “Globally systemic banks that fail will in future be resolved without recourse to the taxpayer and without jeopardising financial stability”.